Efektivitas Perlindungan Hukum Terhadap Peretasan Data Di Pusat Data Nasional - Wijaya, Chessya Tivani; Sujadmiko, Bayu; Zazili, Ahmad (Universitas Sang Bumi Ruwa Jurai, 2025)
The National Data Center which is in the spotlight because it experienced data hacking, this is a serious threat that endangers the security of data and public information in Indonesia. This study aims to examine the effectiveness of legal protection in force in Indonesia against cases of data hacking at the National Data Center. Analyze how effective data protection is at the National Data Center and what Indonesia's strategy is in data protection in the future. The method used in this study is normative juridical by reviewing and analyzing laws and regulations such as the Electronic Information and Transactions Law, the Personal Data Protection Law, and regulations relevant to the study. The results of the study show that the policies issued by Indonesia still face various challenges including the implementation of these regulations to data management resources, and the lack of awareness in personal data protection in the community is a factor that with such a complete policy not supported by public education from it itself, it will not go hand in hand. Therefore, it is necessary to strengthen the policy, increase the capacity of data management resources and update regulations that are adaptive to the threat of cyber dynamics.